2007
DOI: 10.1071/rd06146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestradiol and progesterone on the instant and directional velocity of microsphere movements in the rat oviduct: gap junctions mediate the kinetic effect of oestradiol

Abstract: The oviducal transport of eggs to the uterus normally takes 72-96 h in the rat, but this is reduced to less than 20 h after a single injection of oestradiol (E2). This accelerated transport is associated with an increased frequency of pendular movements in the isthmic segment of the oviduct, with increased levels of the gap junction (GJ) component Connexin (Cx) 43, and is antagonised by progesterone (P). In the present study, we investigated the effect of these hormones on the instant and directional velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The expression of gap junctions in the uterine smooth muscle is controlled by endocrine factors with estrogens enhancing the expression and progesterone suppressing the expression of gap junctions (199, 232, 260, 406,407,408, 533, 563) (for more information see section on expression and trafficking). A very similar mechanism operates in the oviduct, where the number of gap junctions in the smooth muscle cells and the motor activity are increased by estrogens and decreased by progesterone (264,560). These effects are likely to play an important role in propelling the ovum toward the uterine cavity following ovulation.…”
Section: Physiological Function In Cell-to-cell Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of gap junctions in the uterine smooth muscle is controlled by endocrine factors with estrogens enhancing the expression and progesterone suppressing the expression of gap junctions (199, 232, 260, 406,407,408, 533, 563) (for more information see section on expression and trafficking). A very similar mechanism operates in the oviduct, where the number of gap junctions in the smooth muscle cells and the motor activity are increased by estrogens and decreased by progesterone (264,560). These effects are likely to play an important role in propelling the ovum toward the uterine cavity following ovulation.…”
Section: Physiological Function In Cell-to-cell Communicationmentioning
confidence: 99%
“…Connexins are present in the smooth muscle cells of the oviduct and in the uterus, where they play a role in determining the hormonal-dependent motor activity in these tissues (43,202,264,560). The amount of gap junctions in the myometrium increases at the time of labor, and their appearance are necessary for coordinating the contractile activity of the uterine smooth muscle required for the expulsion of the fetus (197, 198, 200,201,202,203, 440, 633).…”
Section: Physiological Function In Cell-to-cell Communicationmentioning
confidence: 99%
“…The single-strand cDNA was synthesized by reverse transcription using the Superscript III Reverse Transcriptase First Strand System for RT-PCR (Invitrogen), according to the manufacturer's protocol. The Light Cycler instrument (Roche Diagnostics, GmbH Mannheim, Germany) was used to quantify the relative transcript level of s100 g, Ampd3, Cyr61 and Tnfip6 while Gapdh was chosen as the housekeeping gene for load control because we have previously demonstrated that E 2 or pregnancy did not affect its expression [9,12]. The SYBR ® Green I double-strand DNA binding dye (Roche Diagnostics) was the reagent of choice for these assays.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrocellulose blots were blocked by incubation overnight at 4°C in TTBS (100 mM Tris/HCl pH 7.5, 150 mM NaCl and 0.05% v/v Tween 20) containing 5% nonfat dry milk. Afterward, blots were incubated with anti-rat antibodies for 1 h with a rabbit anti-rat s100 g (Swant, Bellinzona, Switzerland) or with a mouse anti-rat β-actin (clone JLA20, Calbiochem, La Jolla, CA) as load control because expression level does not change in the rat oviduct after E 2 treatment [12] in 1:2500 or 1:5000 dilutions, respectively. Blots were rinsed 5 times for 5 min each in TBS (100 mM Tris/HCl pH 7.5, and 150 mM NaCl) and were incubated for 2 h in TTBS containing 1:5000 dilution of goat anti-rabbit or anti-mouse IgG horseradish peroxidase conjugate (Chemicon International, Temecula, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation